Transforming the print media business in the digital age: A case study at franchiseglobal.com - Tri Raharjo (Mitra Palupi, 2023)
Background: Building a digital marketplace is one of the most important things a company must do if it wants to dominate. Businesses that can survive in the digital age will have the power of digital at their fingertips. This includes, but is not limited to, Media Companies. Purpose: this study aims to provide an overview of the existing phenomena of franchiseglobal.com business strategy in transforming its print media. Design and methods: This research uses a qualitative descriptive research approach. The method of collecting data and information is interview. The data analysis method is descriptive analysis. Results: FranchiseGlobal.com, as an online media portal focused on franchising, licensing and partnership companies, is implementing a digital branding strategy using the digital branding triangle concept with a focus on SEO, social media and website development. FranchiseGlobal.com is attracting an increasing number of visitors (prospective franchise buyers) to its website, namely more than 100,000 monthly visitors or more than 1.2 million per year and 1,460 inquiry forms (business interest forms) in the past year. FranchiseGlobal.com's digital marketing strategy has the involvement of the company's entire management team and teams from different parts of the company. In order to determine the direction of the company, the strategy also uses the marketing mix theory and SWOT analysis.